Strategies to Solve EFL Students’ Problems in Writing - Meiga Rahmanita (Journal of English in Academic and Professional Communication, 2023)
People nowadays have realized that in learning a language, they also need to master the four language skills, including writing. Second language writing, then, is a necessity to be taught in the schools and universities. Yet, many still consider writing as a complex activity since the writers need to deal with the content, mechanical, and readers’ expectation. That makes EFL students encounter many problems in writing. This article aims to share the strategies in teaching writing to solve students’ problems in writing for all level.